2004
DOI: 10.1016/j.peva.2004.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of link-level hybrid FEC/ARQ-SR for wireless links and long-lived TCP traffic

Abstract: Since the TCP protocol uses the loss of packets as an indication of network congestion, its performance degrades over wireless links, which are characterized by a high bit error rate. Different solutions have been proposed to improve the performance of TCP over wireless links, the most promising one being the use of a hybrid model at the link level combining FEC (Forward Error Correction), ARQ-SR (Automatic Repeat Request with Selective Repeat), and an in-order delivery of packets to IP. The drawback of FEC is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…Indeed, substituting d in (14) by its value in (8), setting ν = 0.5, and recalling that α is equal to 1/(bRT T 2 ), we get the square root formula in (15). This can also be obtained from (9), aŝ C(k) = 0 for all k in the case of deterministic inter-loss times.…”
Section: ) Iid Random Losses (General Renewal Process)mentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, substituting d in (14) by its value in (8), setting ν = 0.5, and recalling that α is equal to 1/(bRT T 2 ), we get the square root formula in (15). This can also be obtained from (9), aŝ C(k) = 0 for all k in the case of deterministic inter-loss times.…”
Section: ) Iid Random Losses (General Renewal Process)mentioning
confidence: 90%
“…Formulas that take into account this burstiness can help to predict the impact of coding schemes on TCP connections, and hence to optimize the amount of redundancy that should be added. A model is presented in [9] to optimize the amount of redundancy on a noisy link using a formula for TCP throughput. Another important use of closed-form expressions for the average transmission rate (or equivalently the throughput) is in the design of TCP-friendly applications.…”
Section: Introductionmentioning
confidence: 99%
“…When the condition of stability λ·S < αB is satisfied, we are sure that the TCP transfers are able to end and that they will not be aborted due to lack of bandwidth. In [2], we found that under our assumption on the error process, α is equal to:…”
Section: Model For Tcp Trafficmentioning
confidence: 94%
“…As a result, the effect of link recovery in such networks should be thoroughly analyzed. In earlier work [13], the performance of a series of ARQ mechanisms are analyzed in the link layer without considering the TCP layer effect. In this work, a set of simulations are performed and results are analyzed to show impact of link recovery on TCP's performance.…”
Section: Introductionmentioning
confidence: 99%